PENGEMBANGAN MEDIA PEMBELAJARAN CD (COMPACT DISC) INTERAKTIF PADA MATA PELAJARAN GEOGRAFI MATERI LINGKUNGAN HIDUP UNTUK SISWA KELAS XI SMA NEGERI 7 SEMARANG TAHUN AJARAN 2014/2015 - Fatimah, Ris (Universitas Negeri Semarang, 2016)
The research aimed to analyze the proses of development, the feasibility and affectiveness of instructionalmedia interactive CD geography subjects of environmental materials for Senior High School students ofclass XI. This study is a Research and Development (R & D). Process development using measures of R&Dfrom Sugiyono that has been modified. Instructional media developed using Adobe Flash CS6 applicationscontaining several multimedia components such as materials, drawi, simulations, exercises and games.Media which have been developed subsequently assessed for feasibility by expert media and materials.Results indicate that the instructional media CD interactive very decent with the result of media experts of88,7%, from material experts of 90%. Media tried out through learning in class. Trial was conducted todetermine the effectiveness of instructional media. Instructional media CD interactive was declared effectiveby the results of classical learning completeness â‰¥85%. In addition to the responses of students and teachersInteractive CD media also showed very good response.